Temas geradores no ensino de química : uma análise comparativa entre duas metodologias aplicadas ao ensino de química em duas escolas da rede estadual de Sergipe - Santos, Antônio Hamilton dos (2015)
The direct action of the student in the construction of their knowledge is much discussed by Paulo Freire who generators Theme is used as methodological strategies in the students educational process about the oppressive reality in unequal societies. This is the starting point for the knowledge building process. In this strategy, the classic content is replaced by contents extracted from the practice of life of the students, through their cultural universe research. This research, qualitative, aimed to analyze how this methodology is designed by two teachers and students of chemistry discipline in two schools in the State Network of Basic Education of Sergipe. Search results according to the educator E1 showed that students in the class who developed the lessons with generators subjects showed better performance when compared to those classes whose classes took place through a traditional method according to E2 educator. It was also possible to observe, along with the educators, the difficulties of working with this teaching methodology, especially the resistance to change in methodology and lack of time to study.